A multifaceted intervention package to improve the diagnosis and management of delirium. (2nd October 2014) - Fleet, J.; Chen, S.; Martin, F.C.; Ernst, T.
ABSTRACT: Background: Delirium is a major cause of morbidity and mortality amongst hospital patients. Previous studies have shown that it is often poorly recognized and managed. We wanted to assess the impact of a multifaceted intervention on delirium management. Methods: A pre/post-intervention design was used. The local hospital delirium guideline was adapted into A7 sized cards and A3/A2 posters. Cards were distributed to junior doctors and teaching sessions were held. Computer screen savers were displayed and delirium promotion days held. The pre/post-intervention data were used to audit the following: delirium knowledge through questionnaires, documented use of the confusion assessment method (CAM) and identification and management of eight common precipitating factors. Re-audit was four months post baseline with interventions within this period. χ 2 tests were used for statistical analysis. Results: A convenience sample of randomly selected doctors in postgraduate training posts completed 100 questionnaires and 25 clinical notes were selected via retrospective identification of delirium. Results from questionnaires demonstrated significant improvements in: recognizing CAM as the diagnostic tool for delirium (24% vs. 71%, p < 0.01); identifying haloperidol as first line in pharmacological management (55% vs. 98%, p <0.01) and its correct dose (40% vs. 67%, p <0.01). In clinical practice, there was significant improvement in documentation of CAM for inpatient delirium assessments (0% vs. 77%, p <0.01). Trainees found the delirium card "very helpful" (82%) and carried it with them at all times (70%). Conclusion: This multifaceted intervention increased CAM use in delirium recognition and improved the knowledge of pharmacological management. The delirium card was highly popular.